Cerium-lithium co-doped lanthanum halide scintillation crystal and preparation method and application thereof
By incorporating 6LiBr and MXa into LaX3:Ce crystals, the developed cerium lithium co-doped lanthanum halide scintillation crystals solve the problem of gamma ray in the prior art and non-consistent melting of components, achieving the problem of neutron detectors being insensitive to gamma rays, thus achieving the Efficient neutron-gamma dual-mode detection and neutron-gamma identification improve detection efficiency.
Patent Information
- Application Number
- CN202410751941.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2024-12-17
AI Technical Summary
Existing neutron detectors such as 3He proportional counters are not sensitive to gamma rays, and 3He resources are short of 3He, and lithium-based potassium ice crystals have non-consistent components melting problems, which limits the It is difficult to achieve efficient neutron-gamma identification and detection by the use of materials.
Develop a cerium lithium co-doped lanthanum halide scintillation crystal Cex6LiyMzLa(1-x-y-z)X3-y. By simultaneously doping 6LiBr and MXa into the LaX3:Ce crystal, neutron detection is achieved using 6LiBr and neutron detection, and using MXa to enhance neutron-gamma Distinguishing ability, realize neutron-gamma dual-mode detection, and improve detection efficiency.
It has achieved high-middle-gamma identification ability, high energy resolution, high light output and short attenuation time, improving the efficiency of neutron-gamma detection, and is suitable for domestic security, oil logging and nuclear energy utilization.
Smart Images

Figure CN119145050A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of scintillation crystal materials, and in particular to a cerium-lithium co-doped lanthanum halide scintillation crystal and a preparation method and use thereof. Background Art
[0002] Neutron detection technology is of great significance in national security, oil well logging and nuclear energy utilization. Neutrons are uncharged particles that are mainly produced by nuclear reactions. Charged particles and photons are detected by detecting these charged particles and photons. Neutron radiation background is usually accompanied by gamma-ray interference. In order to accurately detect neutrons, the detector needs to be able to distinguish between neutrons and gamma rays. 3 He proportional counters are the most commonly used neutron detectors, but they are not sensitive to gamma rays and face problems such as global resource shortages. 3 He alternative materials have become a research hotspot both at home and abroad in recent years.
[0003] Lithium-based potassium cryolite scintillation crystals have high light output and excellent neutron-gamma discrimination capabilities. Among them, Cs2LiYCl6:Ce (CLYC:Ce) and Cs2LiLaBr6:Ce (CLLB:Ce) series crystals have received widespread attention. However, due to the problems of non-uniform melting of components in CLYC:Ce and CLLB:Ce crystals, the utilization of materials is partially limited. Therefore, it is of certain significance to develop new scintillation crystals with neutron-gamma discrimination capabilities. Summary of the invention
[0004] The purpose of this application is to provide a cerium-lithium co-doped lanthanum halide scintillation crystal and its preparation method and use, so as to realize neutron-gamma dual-mode detection and improve neutron-gamma discrimination capability and detection efficiency. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a cerium-lithium co-doped lanthanum halide scintillation crystal, the general formula of which is Ce: x 6 Li y M z La (1-x-y-z) X 3-y , wherein 0<x≤0.2, 0<y≤0.05, 0<z≤0.01, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, and X is selected from at least one of Cl or Br.
[0006] In some embodiments of the present application, 0.005≤x≤0.1, 0.01≤y≤0.05, 0.001≤z≤0.005.
[0007] In some embodiments of the present application, the neutron-gamma discrimination factor of the cerium-lithium co-doped lanthanum halide scintillation crystal is 1.5 to 2.
[0008] The second aspect of the present application provides a method for preparing the cerium-lithium co-doped lanthanum halide scintillation crystal provided in the first aspect of the present application, which comprises the following steps:
[0009] (1) Weigh LaBr3, CeBr3, 6 LiBr and MX a solid, mixed and loaded into a crucible; wherein a is 1 or 2, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, X is selected from at least one of Cl or Br, and the LaBr3, CeBr3, 6 LiBr and MX a The purity of the solids is above 99.99%.
[0010] (2) Evacuate the crucible and seal it.
[0011] (3) placing the sealed crucible in the upper temperature zone of a two-stage temperature-controlled descending furnace, heating the upper temperature zone to 820° C. to 900° C., and heating the lower temperature zone to 650° C. to 750° C., and maintaining the temperature until the raw materials in the crucible are completely melted, and then starting the downward device to descend the crucible from the upper temperature zone to the lower temperature zone for downward growth. After the crystal growth is completed, the temperature is lowered to room temperature to obtain a cerium-lithium co-doped lanthanum halide scintillation crystal.
[0012] In some embodiments of the present application, the constant temperature time is 8 h to 24 h.
[0013] In some embodiments of the present application, the descending speed is 0.2 mm / h to 1 mm / h.
[0014] In some embodiments of the present application, the heating rate of the upper temperature zone is 20°C / h to 50°C / h, the heating rate of the lower temperature zone is 20°C / h to 50°C / h, the cooling rate of the upper temperature zone is 15°C / h to 50°C / h, and the cooling rate of the lower temperature zone is 15°C / h to 50°C / h.
[0015] The third aspect of the present application provides a use of the cerium-lithium co-doped lanthanum halide scintillation crystal provided in the first aspect of the present application in neutron-gamma dual-mode detection.
[0016] Beneficial effects of this application:
[0017] The present application provides a cerium-lithium co-doped lanthanum halide scintillation crystal and its preparation method and use. The general formula of the cerium-lithium co-doped lanthanum halide scintillation crystal is Ce x 6 Li y M z La (1-x-y-z) X3-y , wherein 0<x≤0.2, 0<y≤0.05, 0<z≤0.01, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, and X is selected from at least one of Cl or Br. 6 LiBr and MX a (M and X represent the same elements as above, and a is 1 or 2), using 6 LiBr doping is used to achieve neutron detection, and MXa doping is used to improve neutron-gamma discrimination capability. Through MXa doping, it can be used at lower 6 Neutron-gamma detection is achieved at low Li doping concentrations, and the two work together to achieve neutron-gamma dual-mode detection, and further improve the neutron-gamma discrimination ability and detection efficiency of the scintillation crystal. The crystal has the advantages of high neutron-gamma discrimination factor, high energy resolution, high light output, and short decay time.
[0018] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0020] Figure 1 This is a photo of the cerium-lithium co-doped lanthanum halide scintillation crystal prepared in Example 1 of the present application;
[0021] Figure 2 This is a pulse height spectrum of the cerium-lithium co-doped lanthanum halide scintillation crystal prepared in Example 5 of the present application. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0023] Cerium-doped lanthanum bromide (LaBr3:Ce) crystal is a new type of inorganic scintillating crystal that is currently being studied and applied internationally. It is an outstanding representative of the new generation of gamma-ray detection materials and is widely used in environmental monitoring, oil well logging, high-energy physics and other fields. However, it cannot detect neutrons. Therefore, it is of great significance to develop a new type of cerium-lithium co-doped lanthanum halide scintillating crystal with neutron-gamma discrimination capability based on cerium-doped lanthanum bromide crystal.
[0024] In view of this, the first aspect of the present application provides a cerium-lithium co-doped lanthanum halide scintillation crystal, the general formula of the cerium-lithium co-doped lanthanum halide scintillation crystal is Ce x 6 Li y M z La (1-x-y-z) X 3-y , wherein 0<x≤0.2, 0<y≤0.05, 0<z≤0.01, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, and X is selected from at least one of Cl or Br. 6 LiBr and MX a (M and X represent the same elements as above, and a is 1 or 2), using 6 LiBr doping is used to achieve neutron detection, and MXa doping is used to improve neutron-gamma discrimination capability. Through MXa doping, it can be used at lower 6 Neutron-gamma detection is achieved at low Li doping concentrations, and the two work together to achieve neutron-gamma dual-mode detection, and improve the neutron-gamma discrimination ability and detection efficiency of the scintillation crystal. The crystal has the advantages of high neutron-gamma discrimination factor, high energy resolution, high light output, and short decay time.
[0025] The general formula of the cerium-lithium co-doped lanthanum halide scintillation crystal provided in this application is Ce x 6 Li y M z La (1-x-y-z) X 3-y, wherein 0<x≤0.2, 0<y≤0.05, 0<z≤0.01, preferably 0.005≤x≤0.1, 0.01≤y≤0.05, 0.001≤z≤0.005. For example, the value of x can be 0.001, 0.005, 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.17, 0.2, or a range consisting of any two of them, the value of y can be 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, or a range consisting of any two of them, and the value of z can be 0.001, 0.003, 0.004, 0.005, 0.006, 0.008, 0.01, or a range consisting of any two of them. When x, y or z exceeds the above range, the crystal transparency decreases and the quality deteriorates, which will directly lead to a decrease in the crystal light output, energy resolution and neutron-gamma discrimination ability. By regulating the values of x, y and z within the above range, it is beneficial to obtain a cerium-lithium co-doped lanthanum halide scintillator crystal with high transparency, integrity, no cracks, and good component melting consistency, which has high neutron-gamma discrimination ability, energy resolution and light output, and a shorter decay time. M is selected from the elements within the above range, which is beneficial to improving the energy resolution and neutron-gamma discrimination ability of the crystal; X is selected from the elements within the above range, which is beneficial to obtaining a uniformly melted crystal.
[0026] In some embodiments of the present application, the neutron-gamma discrimination factor (FOM) of the cerium-lithium co-doped lanthanum halide scintillation crystal is 1.5 to 2, for example, the value of FOM can be 1.5, 1.6, 1.7, 1.8, 1.9, 2 or a range consisting of any two values therein. The cerium-lithium co-doped lanthanum halide scintillation crystal with a FOM value within the above range can achieve neutron-gamma dual-mode detection while having a high neutron-gamma discrimination capability.
[0027] The second aspect of the present application provides a method for preparing the cerium-lithium co-doped lanthanum halide scintillation crystal provided in the first aspect of the present application, which comprises the following steps:
[0028] (1) Weigh LaBr3, CeBr3, 6 LiBr and MX a solid, mixed and loaded into a crucible; wherein a is 1 or 2, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, X is selected from at least one of Cl or Br, and the LaBr3, CeBr3, 6 LiBr and MX a The purity of the solids is above 99.99%.
[0029] (2) Evacuate the crucible and seal it.
[0030] (3) placing the sealed crucible in the upper temperature zone of a two-stage temperature-controlled descending furnace, heating the upper temperature zone to 820° C. to 900° C., and heating the lower temperature zone to 650° C. to 750° C., and maintaining the temperature until the raw materials in the crucible are completely melted, and then starting the downward device to descend the crucible from the upper temperature zone to the lower temperature zone for downward growth. After the crystal growth is completed, the temperature is lowered to room temperature to obtain a cerium-lithium co-doped lanthanum halide scintillation crystal.
[0031] The cerium-lithium co-doped lanthanum halide scintillating crystal prepared by the above method is doped into the LaX3:Ce crystal at the same time. 6 LiBr and MX a ,use 6 LiBr doping is used to achieve neutron detection, and MXa doping is used to improve neutron-gamma discrimination capability. Through MXa doping, it can be used at lower 6 Neutron-gamma detection is achieved at low Li doping concentrations. The two work synergistically to achieve neutron-gamma dual-mode detection and improve the neutron-gamma discrimination capability and detection efficiency of the crystal.
[0032] In some embodiments of the present application, the temperature of the upper temperature zone is 820°C to 900°C, and the temperature of the lower temperature zone is 650°C to 750°C. For example, the temperature of the upper temperature zone can be 820°C, 830°C, 840°C, 850°C, 860°C, 880°C, 900°C, or a range consisting of any two of the values, and the temperature of the lower temperature zone can be 650°C, 656°C, 680°C, 700°C, 712°C, 725°C, 740, 750°C, or a range consisting of any two of the values. Regulating the temperatures of the upper and lower temperature zones within the above range is conducive to forming a suitable temperature gradient, ensuring that the raw materials are completely melted in the upper temperature zone, and crystal growth is carried out in the lower temperature zone.
[0033] In some embodiments of the present application, MX a It can be selected from NaCl, MgCl2, CaCl2, SrCl2, BaCl2, ZnCl2, NaBr, MgBr2, CaBr2, SrBr2, BaBr2, ZnBr2, etc. The use of the above substances to dope lanthanum halide scintillation crystals can optimize the energy nonlinear response of the crystals, which is conducive to further improving the neutron-gamma discrimination ability and detection efficiency of the crystals.
[0034] In the above step (1), LaBr3, CeBr3, 6 LiBr and MX a The raw materials can be added according to the molar ratio of each element in the general formula of the desired cerium-lithium co-doped lanthanum halide scintillation crystal. 6 LiBr and MX aUsually it is a high-purity reagent with water and oxygen content less than 100ppm and purity greater than 99.99%. 6 LiBr and MX a When the purity is within the above range, the influence of water molecules and other impurities on the purity of the final cerium-lithium co-doped lanthanum halide scintillation crystal can be reduced, while the defects introduced by the oxide can be avoided, thereby improving the optical quality of the cerium-lithium co-doped lanthanum halide scintillation crystal.
[0035] In the above step (1), weigh LaBr3, CeBr3, 6 LiBr and MX a The solid step should be carried out under anhydrous and low-oxygen conditions to reduce the reaction of water and oxygen introduced from the environment with the final cerium-lithium co-doped lanthanum halide scintillation crystals. For example, the above solid raw materials can be weighed in a glove box with a water content of ≤0.1ppm and an oxygen content of ≤0.1ppm.
[0036] The present application has no particular limitation on the vacuum degree in step (2), as long as the purpose of the present application can be achieved. For example, the vacuum degree can be 10 -3 Pa to 10 -5 Pa. The present application has no particular restrictions on the sealing method in step (2), as long as the purpose of the present application can be achieved. For example, the tube mouth of the crucible can be sealed by an oxyhydrogen flame to achieve the purpose of isolating water and oxygen. The present application has no particular restrictions on the type of crucible, as long as the purpose of the present application can be achieved. For example, a quartz crucible can be used. In the present application, room temperature refers to 15°C to 35°C.
[0037] In some embodiments of the present application, the constant temperature time is 8 hours to 24 hours, for example, the constant temperature time can be 8 hours, 10 hours, 12 hours, 14 hours, 15 hours, 17 hours, 19 hours, 21 hours, 24 hours or a range consisting of any two of these values. When the constant temperature time is within the above range, the raw materials can be completely melted, which is conducive to obtaining a complete, crack-free, and component-melting-consistent cerium-lithium co-doped lanthanum halide scintillation crystal; at the same time, energy consumption can be minimized.
[0038] In some embodiments of the present application, the falling speed is 0.2 mm / h to 1 mm / h. For example, the falling speed can be 0.2 mm / h, 0.4 mm / h, 0.5 mm / h, 0.7 mm / h, 0.8 mm / h, 0.9 mm / h, 1 mm / h, or a range consisting of any two of the values. Regulating the falling speed within the above range is conducive to the growth of the crystal, thereby obtaining a complete, crack-free, and internally high-quality cerium-lithium co-doped lanthanum halide scintillation crystal.
[0039] In some embodiments of the present application, the heating rate of the upper temperature zone is 20°C / h to 50°C / h, the heating rate of the lower temperature zone is 20°C / h to 50°C / h, the cooling rate of the upper temperature zone is 15°C / h to 50°C / h, and the cooling rate of the lower temperature zone is 15°C / h to 50°C / h. For example, the heating rate of the upper temperature zone or the lower temperature zone can be 20°C / h, 25°C / h, 30°C / h, 35°C / h, 40°C / h, 45°C / h, 50°C / h, or a range consisting of any two values therein, and the cooling rate of the upper temperature zone or the lower temperature zone can be 15°C / h, 20°C / h, 25°C / h, 30°C / h, 35°C / h, 40°C / h, 45°C / h, 50°C / h, or a range consisting of any two values therein. Regulating the above-mentioned heating rate and cooling rate within the above-mentioned range is beneficial to the growth of the crystal, thereby obtaining a complete, crack-free cerium-lithium co-doped lanthanum halide scintillation crystal.
[0040] The third aspect of the present application provides a use of the cerium-lithium co-doped lanthanum halide scintillation crystal provided in the first aspect of the present application in neutron-gamma dual-mode detection. The cerium-lithium co-doped lanthanum halide scintillation crystal of the present application is applied to neutron-gamma dual-mode detection, which has a high neutron-gamma discrimination capability and a high detection efficiency.
[0041] Example
[0042] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0043] Test methods and equipment:
[0044] Scintillating crystal composition test:
[0045] The crystals prepared in each embodiment and comparative example were ground into powder using a mortar in a vacuum glove, and then vacuumed and sealed to obtain test samples. The content of each element in the crystal was measured by inductively coupled plasma optical emission spectrometry (ICP-OES), thereby confirming the chemical formula of the crystal.
[0046] Energy resolution test:
[0047] Energy resolution test was carried out according to the method specified in Chapter 7 of GB / T 13181-2002 "Scintillator Performance Measurement Method". The radiation source was 137 Cs (662keV) rays were used to measure the crystals of each embodiment and comparative example. 137 The pulse height spectrum under the Cs radiation source is analyzed to obtain its energy resolution. In the energy resolution test, the smaller the energy resolution value, the higher the energy resolution of the crystal.
[0048] Neutron-Gamma Discrimination Factor Test:
[0049] The neutron-gamma discrimination factor of the crystal is calculated using 137 Cs and 252 Cf was used as the excitation source, and the photomultiplier tube collected the luminescence signal, which was directly recorded by the digitizer. The software ROOT was used for offline data processing to obtain the average gamma and neutron waveforms, and the waveforms were analyzed to obtain the neutron-gamma discrimination factor (FOM).
[0050] Light output test:
[0051] According to the provisions of 5.1 Full Absorption Peak Method or Compton Distribution Edge Method in the national standard GB / T13181-2002 Scintillator Performance Measurement Method, the light output of the crystals of each embodiment and comparative example is tested. In this application, the full absorption peak method is used for testing.
[0052] Decay time test:
[0053] The decay time test was carried out according to the single photon method specified in 10.4 of the national standard GB / T 13181-2002 "Scintillator Performance Measurement Method". The radiation source was 137 Cs (662keV) rays. The crystals of each embodiment and comparative example were measured at 137 Decay time under Cs radiation source. The shorter the decay time, the faster the response speed and the higher the detection efficiency.
[0054] Example 1
[0055] Raw material weighing: In a glove box with a water content of ≤0.1ppm and an oxygen content of ≤0.1ppm, accurately weigh 100g of anhydrous, 99.99% pure LaBr3 raw material, 5.42g of CeBr3 raw material, 6 0.49 g of LiBr raw material and 0.28 g of SrBr2 raw material were mixed evenly in an agate mortar and then placed in a pre-cleaned quartz crucible.
[0056] Crucible sealing: After taking the quartz crucible out of the glove box, evacuate it to 10 -3 Pa, use hydrogen-oxygen flame to seal the tube mouth of the quartz crucible to achieve the purpose of isolating water and oxygen.
[0057] Crystal growth: Place the quartz crucible in the upper temperature zone of a two-stage temperature-controlled descending furnace, raise the temperature of the upper temperature zone to 870°C at a heating rate of 35°C / h, and raise the temperature of the lower temperature zone to 750°C at a heating rate of 25°C / h. Keep the temperature constant for 12 hours to completely melt the raw materials in the crucible. Then lower the quartz crucible in the furnace at a descending speed of v=0.2mm / h to guide the crystal downward growth. The crystal begins to nucleate and grow from the bottom of the crucible. Lower until the quartz crucible enters the lower temperature zone completely. After the crystal growth is completed, stop descending. Then lower the upper temperature zone to room temperature at a cooling rate of 20°C / h, and lower the lower temperature zone to room temperature at a cooling rate of 30°C / h, and take out the crystal.
[0058] Example 2 to Example 10
[0059] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.
[0060] Comparative Example 1
[0061] Weighing of raw materials: In a glove box with a water content of ≤0.1ppm and an oxygen content of ≤0.1ppm, accurately weigh 100g of anhydrous LaBr3 raw material with a purity of 99.99% and 5.28g of CeBr3 raw material, mix them evenly in an agate mortar, and then place them in a pre-cleaned quartz crucible.
[0062] Crucible sealing: After taking the quartz crucible out of the glove box, evacuate it to 10 -3 Pa, use hydrogen-oxygen flame to seal the tube mouth of the quartz crucible to achieve the purpose of isolating water and oxygen.
[0063] Crystal growth: Place the quartz crucible in the upper temperature zone of a two-stage temperature-controlled descending furnace, raise the temperature of the upper temperature zone to 870°C at a heating rate of 35°C / h, and raise the temperature of the lower temperature zone to 750°C at a heating rate of 25°C / h. Keep the temperature constant for 12 hours to completely melt the raw materials in the crucible. Then lower the quartz crucible in the furnace at a descending speed of v=0.6mm / h to guide the crystal downward growth. The crystal begins to nucleate and grow from the bottom of the crucible. Lower until the quartz crucible enters the lower temperature zone. After the crystal growth is completed, stop descending. Then lower the upper temperature zone to room temperature at a cooling rate of 20°C / h, and lower the lower temperature zone to room temperature at a cooling rate of 30°C / h, and take out the crystal.
[0064] Comparative Example 2
[0065] Weighing of raw materials: In a glove box with a water content of ≤0.1ppm and an oxygen content of ≤0.1ppm, accurately weigh 105.1g of anhydrous CsBr raw material with a purity of 99.99%, 21.45g of LiBr raw material, 92.46g of LaBr3 raw material, and 0.94g of CeBr3 raw material, mix them evenly in an agate mortar, and then put them into a pre-cleaned quartz crucible.
[0066] Crucible sealing: After taking the quartz crucible out of the glove box, evacuate it to 10 -3 Pa, use hydrogen-oxygen flame to seal the tube mouth of the quartz crucible to achieve the purpose of isolating water and oxygen.
[0067] Crystal growth: Place the crucible into the ceramic down-conductor, then place the down-conductor on the down-conductor mechanism, and raise the bottom of the crucible to the appropriate position on the upper edge of the temperature gradient zone in the descending furnace, so that the bottom of the crucible is heated to 560°C, and the temperature gradient of the growth interface is 20°C / mm; heat the raw materials to a molten state and keep them warm for 20 hours; lower the quartz crucible at a speed of 0.3mm / h through the down-conductor mechanism until the melt is completely solidified and crystallized, and cool it down to room temperature at a cooling rate of 15°C / h. The general formula of the crystal composition is Cs2LiLa 0.99 Ce 0.01 Br6.
[0068] Comparative Example 3
[0069] Growth 6 Alkaline earth metal doped NaI with a Li atomic percentage of 2.0%, a Tl atomic percentage of 0.2%, and a MgI2 atomic percentage of 0.1%: 6 Li, Tl crystals.
[0070] Weigh 82.22g of NaI, 6 LiF 0.82 g, TlI 0.37 g, and MgI2 0.16 g were mixed, placed in a conical-bottom quartz crucible and sealed.
[0071] Place the sealed quartz crucible vertically in the middle of the descending crystal growth furnace, heat the crystal growth furnace to 850℃ and keep it warm until the raw materials are completely melted and mixed evenly; adjust the crucible position and furnace temperature to reduce the bottom temperature of the crucible to the melting point of the scintillation crystal, and then lower the quartz crucible in the furnace at a descending speed of 1mm / h. The crystal begins to nucleate and grow from the bottom of the crucible until the melt is completely solidified and crystallized. Reduce the furnace temperature at a rate of 15℃ / h. When the thermocouple shows that it has dropped to room temperature, take out the alkaline earth metal-doped NaI: 6 Li, Tl crystal, the crystal composition formula is (Na 0.977 6 Li 0.02 Tl 0.002 Mg 0.001 )I.
[0072] Comparative Examples 4 to 6
[0073] Except for adjusting the relevant parameters according to Table 1, the rest is the same as Example 1.
[0074] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.
[0075] Table 1
[0076]
[0077]
[0078] Note: " / " in Table 1 indicates that there is no corresponding parameter or substance. The scintillation decay time of the crystal sample of Comparative Example 3 is fitted by a double exponential function, and the fast component of its decay time is 213ns, accounting for 10%; the slow component is 1250ns, accounting for 90%.
[0079] The inventors found that the crystals obtained in Examples 1 to 10 were complete, transparent, and had good component consistency. The crystals obtained in Comparative Examples 4 to 6 had low transparency.
[0080] It can be seen from Examples 1 to 10 and Comparative Examples 1 to 6 that the cerium-lithium co-doped lanthanum halide scintillation crystal provided by the present application is prepared by simultaneously doping LaX3:Ce into the crystal. 6 LiBr and MX a , while regulating the values of x, y, and z within the scope of this application, neutron-gamma dual-mode detection can be achieved, and it has a high neutron-gamma discrimination capability, and has the advantages of high energy resolution, high light output, and short decay time. The LaBr3:Ce crystal in Comparative Example 1 can detect gamma rays, but cannot detect neutrons. The Cs2LiLaBr6:Ce (CLLB:Ce) crystal in Comparative Example 2 is unstable at high temperatures, and part of the crystals spontaneously crystallized from the melt may not be CLLB:Ce, which has the problem of non-uniform melting of components, and the FOM value is low, and the decay time is long. The Mg-doped lithium thallium co-doped sodium iodide scintillation crystal in Comparative Example 3 has a high FOM and energy resolution, but its decay time is long, and the time for neutron-gamma ray detection is long, and the detection efficiency is low. In Comparative Examples 4 to 6, the values of x, y or z are not within the scope of the present application. The crystals obtained in the above comparative examples are of poor quality and too low transparency. FOM, energy resolution, light output and decay time tests were not performed.
[0081] from Figure 1 It can be seen that the cerium-lithium co-doped lanthanum halide scintillation crystal prepared in Example 1 is complete, transparent, and has good component consistency.
[0082] Figure 2 The pulse height spectrum of the cerium-lithium co-doped lanthanum halide scintillation crystal prepared in Example 5 is shown. Figure 2It can be seen that the energy resolution of the cerium-lithium co-doped lanthanum halide scintillation crystal of Example 5 is 2.8%@662keV, which is less than the energy resolution of the Mg-doped lithium-thallium co-doped sodium iodide scintillation crystal in Comparative Example 3, indicating that the cerium-lithium co-doped lanthanum halide scintillation crystal provided in the present application can achieve higher energy resolution.
[0083] Therefore, the cerium-lithium co-doped lanthanum halide scintillator crystal provided by the present application can realize neutron-gamma dual-mode detection while also improving the neutron-gamma discrimination capability and detection efficiency of the crystal. The crystal has the advantages of high FOM, high energy resolution, high light output, short decay time, etc., and can be widely used in the fields of homeland security, oil well logging, and nuclear energy utilization.
[0084] It should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0085] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0086] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A cerium-lithium co-doped lanthanum halide scintillation crystal, wherein the general formula of the cerium-lithium co-doped lanthanum halide scintillation crystal is Ce x 6 Li y M z La (1-x-y-z) X 3-y , in, 0<x≤0.2, 0<y≤0.05, 0<z≤0.01, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, and X is selected from at least one of Cl or Br.
2. The cerium-lithium co-doped lanthanum halide scintillation crystal according to claim 1, in, 0.005≤x≤0.1, 0.01≤y≤0.05, 0.001≤z≤0.
005.
3. The cerium-lithium co-doped lanthanum halide scintillation crystal according to claim 1, in, The neutron-gamma discrimination factor of the cerium-lithium co-doped lanthanum halide scintillation crystal is 1.5 to 2.
4. A method for preparing a cerium-lithium co-doped lanthanum halide scintillation crystal according to any one of claims 1 to 3, wherein The following steps are involved: (1) Weigh LaBr 3 , CeBr 3 , 6 LiBr and MX a solid, mixed and loaded into a crucible; wherein a is 1 or 2, M is selected from at least one of Na, Mg, Ca, Sr, Ba or Zn, X is selected from at least one of Cl or Br, the LaBr 3 , CeBr 3 , 6 LiBr and MX a The purity of solids is above 99.99%; (2) evacuating the crucible and sealing it; (3) placing the sealed crucible in the upper temperature zone of a two-stage temperature-controlled descending furnace, heating the upper temperature zone to 820° C. to 900° C., and heating the lower temperature zone to 650° C. to 750° C., and maintaining the temperature until the raw materials in the crucible are completely melted, and then starting the downward device to allow the crucible to descend from the upper temperature zone to the lower temperature zone for downward growth. After the crystal growth is completed, the crucible is cooled to room temperature to obtain the cerium-lithium co-doped lanthanum halide scintillation crystal.
5. The preparation method according to claim 4, in, The constant temperature time is 8h to 24h.
6. The preparation method according to claim 4, in, The descending speed is 0.2 mm / h to 1 mm / h.
7. The preparation method according to claim 4, in, The heating rate of the upper temperature zone is 20°C / h to 50°C / h, the heating rate of the lower temperature zone is 20°C / h to 50°C / h, the cooling rate of the upper temperature zone is 15°C / h to 50°C / h, and the cooling rate of the lower temperature zone is 15°C / h to 50°C / h.
8. Use of the cerium-lithium co-doped lanthanum halide scintillation crystal according to any one of claims 1 to 3 in neutron-gamma dual-mode detection.
